2016
DOI: 10.18332/tpc/65229
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Retail ‘Vape Shops’ in the San Francisco Bay Area

Abstract: INTRODUCTION The use of electronic cigarettes or vape devices is increasing, and products are evolving rapidly. This study assessed retail vape shops in the San Francisco Bay Area to describe store characteristics, products offered, advertisements and health claims, as well as employees’ perceptions of their customers’ demographics, and practices to support smoking cessation. METHODS We conducted store audits of shops that exclusively sell vape devices with physical addresses in San Francisco and Alameda cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…These patterns are consistent with research that suggests vape shops focus primarily on newer generation devices and encourage users’ experimentation with a variety of nicotine and e-liquid options [ 20 - 22 ]. Studies also indicate vape shop employees frequently characterize e-cigarettes as smoking cessation devices and, despite lack of formal training, provide counsel regarding smoking cessation to customers [ 8 , 23 ].…”
Section: Discussionsupporting
confidence: 82%
“…These patterns are consistent with research that suggests vape shops focus primarily on newer generation devices and encourage users’ experimentation with a variety of nicotine and e-liquid options [ 20 - 22 ]. Studies also indicate vape shop employees frequently characterize e-cigarettes as smoking cessation devices and, despite lack of formal training, provide counsel regarding smoking cessation to customers [ 8 , 23 ].…”
Section: Discussionsupporting
confidence: 82%
“…Visual resemblance to cigarettes and being disposable (rather than rechargeable) elicited negative responses towards cigalike advertisements. Some of the negative reactions may have been informed by the fact that big tobacco companies manufactured mainly cigalikes at the time of the study [62], while 'independent' vape shops were the source for large vaporizers [64].…”
Section: Discussionmentioning
confidence: 99%
“…Existing US vape shop research shows that most staff have personal experience of using e-cigarettes to quit tobacco, hold strong beliefs regarding the health benefits and safety of e-cigarettes, and their ability to help smokers quit [ 34 , 35 , 36 ]. Vape shop observations showed that they extensively promoted their products and offered cessation related product advice [ 36 , 37 ], as well as offering a place of recreation [ 38 ]. One study showed that the most successful shops were more likely to be endorsed in online reviews for: helping to fix devices, having ‘helpful/patient/respectful staff’, and a ‘bar type’ environment [ 39 ] (p. 1).…”
Section: Introductionmentioning
confidence: 99%